DOI: 10.35537/10915/67760
|View full text |Cite
|
Sign up to set email alerts
|

Impacto de agroquímicos sobre los ensambles de macroinvertebrados en arroyos rurales

Abstract: La creciente adopción de sistemas productivos basados en la siembra directa, junto con el uso de agroquímicos y la introducción de semillas modificadas genéticamente permitió extender la superficie sembrada de los cultivos, principalmente de soja. Es en el sur de América Latina donde este cambio tecnológico se ha implementado con mayor velocidad e intensidad. En Argentina, el área sembrada del cultivo de soja aumentó de 4,9 a 20,5 millones de hectáreas desde la campaña 90/91 hasta el presente; en Brasil, el ár… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…In recent years, the use of agrochemicals, as well as genetically modified seeds, has been increasing. The consumption of agrochemicals and fertilizers has contaminated streams that affect fauna and aquatic ecosystems (Marrochi, 2018). It has been shown that the inappropriate use of agrochemicals affects the ecological balance (Moreno, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the use of agrochemicals, as well as genetically modified seeds, has been increasing. The consumption of agrochemicals and fertilizers has contaminated streams that affect fauna and aquatic ecosystems (Marrochi, 2018). It has been shown that the inappropriate use of agrochemicals affects the ecological balance (Moreno, 2017).…”
Section: Introductionmentioning
confidence: 99%